Identifying target groups for livestock improvement research: the classification of sedentary livestock producers in western Niger - Williams, Timothy O. (Elsevier, 1994)
Classification constitutes an essential step in any realistic evaluation of the constraints and opportunities that exist within a farming system. In this study, cluster analysis was used to classify crop-livestock producers in three villages in western Niger into recommendation domains using a combination of production and marketing variables. Four recommendation domains were identified. Discriminant analysis was used to profile the characteristics of the obtained groups. Cluster and discriminant analysis results were used to suggest appropriate research and policy interventions for each grouThe approach utilized represents a logical and systematic method of classification which is deemed appropriate for determining the factors which affect livestock productivity and hence identifying research and policy interventions to meet producers' needs.